اتجاهات الدراسات النقدية في الشعرِ العربِي الخليجي الحديث :‏ ‏دراسة تحليلية /‏ - بن عربي، خليفة ياسين
In this thesis an attempt has been made to track the most significant critical studies of modern Arab poetry in the Arabian Gulf region. The major aim of this study is to define the most important studies in critical analysis of modern Arab poetry in the Arabian Gulf to readers and researchers, and to stress its status in Arab poetry studies. It further aims to elaborate the efforts of pioneer critics in modern Arabian Gulf poetry, and also serves as an attempt to enrich the field of studies in criticism and their literary trends. A total of seventeen studies of academic nature have been carefully selected in order to include different trends in critical analysis, which include social, artistic, structural, interpretive and Islamic trends. An effort is then made to analyze the critical approach of the selected studies, by using of analytical and inductive methods in an attempt to trace them back to their methodological roots, and to examine the degree of their relevance to the trends they belong to, and to examine their ability to benefit from modern analytical methodologies. Each study was conducted with a thorough investigation of its theology that elaborates its most significant features. In conclusion this study was able to establish the fact that most contemporary studies in Arab poetry in the Arabian Gulf region are comprehensive, and they contain clear methodological elements.